Kinerja Keuangan Pemerintah Desa di Masa Pandemi Covid 19, Studi Kasus Desa Lapara Kec. Siompu Kab. Buton Selatan - Winda Ayu Virginia; Rusman Ramli (Politeknik Baubau, 2022)
Good financial management will have an impact on good financial performance which can be measured by several indicators. This study aims to analyze the financial performance of the Village Government before and during the Covid 19 pandemic. This research was conducted in Lapara Village, Siompu District, South Buton Regency, Southeast Sulawesi Province. The data collected is secondary data, namely the Lapara Village APBDes in 2019 and 2020. The data analysis technique in this study is a quantitative descriptive of the Lapara Village APBDes using two performance indicators, namely effectiveness and efficiency. The results of this study indicate that the Financial Performance of Lapara Village, Siompu District, South Buton Regency before and during the Covid 19 Pandemic did not change and was included in the fairly effective category with an effectiveness value range of 90-100%. Using efficiency analysis, it was also found that both before the pandemic and during the Covid-19 pandemic, the category was less efficient, namely before the pandemic was 93.96% and after the pandemic was 97.12%. This study also found that there was an increase in the realization of the APBDes in Lapara Village before and during the Covid 19 pandemic.